2023
DOI: 10.3390/ijms242417221
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptomic Analysis Reveals That Melatonin Alleviates Aluminum Toxicity in Alfalfa (Medicago sativa L.)

Congge Liu,
Haijing Cheng,
Shuwei Wang
et al.

Abstract: Aluminum (Al) toxicity is the most common factor limiting the growth of alfalfa in acidic soil conditions. Melatonin (MT), a significant pleiotropic molecule present in both plants and animals, has shown promise in mitigating Al toxicity in various plant species. This study aims to elucidate the underlying mechanism by which melatonin alleviates Al toxicity in alfalfa through a combined physiological and transcriptomic analysis. The results reveal that the addition of 5 μM melatonin significantly increased alf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Subsequently, 4 g of sodium hydroxide and 1 g of sodium peroxide was added to the mixture, which was then melted in a muffle furnace at 650 °C for 15 min. The resulting solution was filtered, and the total amount of Al was quantified by FAAS at 324.7 nm [ 47 ]. Al content was localized in roots by Chrome Azurol S staining.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 4 g of sodium hydroxide and 1 g of sodium peroxide was added to the mixture, which was then melted in a muffle furnace at 650 °C for 15 min. The resulting solution was filtered, and the total amount of Al was quantified by FAAS at 324.7 nm [ 47 ]. Al content was localized in roots by Chrome Azurol S staining.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of the enzyme ascorbate peroxidase (APX; EC 1.11.1.11) was measured by monitoring the reduction in absorbance at 290 nm caused by the oxidation of ascorbic acid by the APX-H 2 O 2 complex. The unit (U) of APX activity is defined as the oxidation of 1 M of ascorbate per minute per gram of root sample [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions encompass the facilitation of seed germination and root growth, optimization of photosynthetic processes as well as the augmentation of osmoregulation [21][22][23]. Several studies have demonstrated that MT can mitigate plant damage induced by Ni stress through modulation of the antioxidant system and scavenging excessive ROS [24,25]. Meanwhile, MT can increase the accumulation of nutrients and improve the resistance of plants to heavy metal stress by enhancing photosynthesis, regulating the gene expression of plant hormone signal transduction (IAA, ABA, GA, etc.…”
Section: Introductionmentioning
confidence: 99%